Integration of micro-sensor technology and remote sensing for monitoring coastal water quality in a municipal beach and other areas in Cyprus - Hadjimitsis, Diofantos G.; Themistocleous, Kyriacos; Agapiou, Athos; Hadjimitsis, Marinos G. (My University, 2009)
The proposed project has as main objective the monitoring of coastal waters using satellite remote sensing and wireless sensor technology employed on a buoy with emphasis firstly in municipal beaches and further to areas that a systematic sampling is required. Satellite remote sensing has the advantage of using remote sensing data to assess the quality of water bodies has proven to be successful not only in inland waters but to coastal water areas as shown by several others conducted studies. Reflectance signature of municipal coastal water is monitored using a GER 1500 field spectroradiometer. Simultaneous measurements of turbidity, temperature have been acquired. Cross-validation of measurements of water quality both from micro-sensor and remote sensing are planned to be undertaken. An overall methodology that integrates both micro-sensor technology and satellite remote sensing is presented
Keywords: Remote sensing; Agriculture; Beaches; Hydrology; Satellites; Turbidity; Water--Pollution; Water quality